2021
DOI: 10.1111/nan.12756
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of perilipins in human brain during aging and in Alzheimer's disease

Abstract: Aims Perilipins are conserved proteins that decorate intracellular lipid droplets and are essential for lipid metabolism. To date, there is limited knowledge on their expression in human brain or their involvement in brain aging and neurodegeneration. The aim of this study was to characterise the expression levels of perilipins (Plin1–Plin5) in different cerebral areas from subjects of different age, with or without signs of neurodegeneration. Methods We performed real‐time RT‐PCR, western blotting, immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 63 publications
(103 reference statements)
0
12
1
Order By: Relevance
“…Moreover, an accumulation of LD-containing cells (lipid-laden cells), associated with PLIN2 expression, was observed in meningeal, cortical and neurogenic brain regions of the aging mice [ 73 ]. Finally, a recent expression study on all human perlipin proteins (PLIN1-5), found that PLIN2 accumulates, particularly in neurons, in brains of old subjects and of patients with Alzheimer disease [ 74 ]. As an alternative putative mechanism regulating LD level, it was shown that targeted degradation of PLIN2 and PLIN3 occurs by chaperone-mediated autophagy (CMA) [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an accumulation of LD-containing cells (lipid-laden cells), associated with PLIN2 expression, was observed in meningeal, cortical and neurogenic brain regions of the aging mice [ 73 ]. Finally, a recent expression study on all human perlipin proteins (PLIN1-5), found that PLIN2 accumulates, particularly in neurons, in brains of old subjects and of patients with Alzheimer disease [ 74 ]. As an alternative putative mechanism regulating LD level, it was shown that targeted degradation of PLIN2 and PLIN3 occurs by chaperone-mediated autophagy (CMA) [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, lipid droplets (LDs), the organelles that serve as a storage of neutral lipids [64], accumulate in AD [65]. The expression of perilipin-2 (Plin2, a specific surface marker of LD), but not other perilipin family members, is selectively upregulated in the frontal cortex [66]. Increased neutral lipids and LDs in post-mortem AD brains, AD patient-derived fibroblasts [67], and peripheral blood mononuclear cells [68] collectively signify disrupted neutral lipid metabolism in AD (see reviews [69,70]).…”
Section: Glycerolipidsmentioning
confidence: 99%
“…Regarding lipid metabolism, we observed a significant decrease of PLIN2 and PLIN3 expression in the ENR group. Very recently, it was demonstrated that PLIN2 in the brain is the only PLIN family member that is modulated with age and neuroinflammation, suggesting that PLIN2 may be connected with the brain, aging and inflammation [68]. Therefore, the decrease in PLIN2 expression in the ENR group suggests that PUFA ω-3 can prevent lipid accumulation and, consequently, possibly lipotoxicity and thus inflammation.…”
Section: Brainmentioning
confidence: 99%